Faktor-faktor Yang Memengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Di Kota Pekanbaru - Ultsani, Mila; Agustiawan, Agustiawan; Fitriana, Nur (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to determine the factors influencing taxpayer compliance when paying motor vehicle tax at UPT SAMSAT Simpang Tiga, Pekanbaru City. This research uses quantitative methods. The population used in this research are taxpayers who pay their vehicle tax at UPT SAMSAT Simpang Tiga Pekanbaru City. The sample used in this research was 400 taxpayers. This research data was collected by distributing questionnaires directly to UPT SAMSAT Simpang Tiga Pekanbaru City. The analysis used in this research is multiple linear regression analysis with SPSS version 22 software tools. The results of this study show that the factors used, namely taxpayer income level, taxpayer awareness, service quality, and tax sanctions have an influence on motor vehicle taxpayer compliance.